Promises and reservations towards science and technology among South African publics: A culture-sensitive approach. (January 2018) - Guenther, Lars; Weingart, Peter
Against the background that surveys measuring public perceptions of science and technology are often removed from cultural contexts and do not equally represent all regions of the world, this study investigated attitudes towards science and technology among different publics of the South African population. To apply a culture-sensitive approach, theoretical considerations of cultural distance were combined with methodological considerations of segmentation studies, and representative data ( n  = 3183) were reanalysed. The findings show that six South African publics can be distinguished, and that – despite the fact that all publics see more promises of science than reservations – there tend to be sensitive differences between these publics. In the long run, such findings might help to make science communication more effective.